IRONI DAN LOGIKA REALITAS DALAM CERPEN CLARA - Heksa Biopsi Puji Hastuti (SAWERIGADING, 2012)
"Clara" short story tells about the riots of May 1998. The storytelingfocuses on crimes and immoral violence comitted by a group of people to Clara, a Chinese-Indonesian girl. The real historical settings raises questions about irony and logic of reality described in the short story. This study aims to explain the condition. The data was analyzed by usingformalstructure theory and by applying sociological approach in interpretating the implicit intentions of the writer. The result of analysis showed that there were some irony descriptions of what happened in Indonesia, namely: the corruption that made this wealthy country looked poor and helpless, engineering reports, and officer of information provider that actually hid information. Those three kinds of deed were done by uniformed officers. Other kind of irony done by people was hatred to certain ethnic without considereing whether or not she was a good person. Meanwhile, the logic of reality in the short story "Clara" confirmed with the news contained in the mass media. Storytelling implicitlyprovided a counterweight to the growing negative suspicions in the community with news in mass media after riots based on the testimony of several sources. Abstrak Cerpen "Clara" mengisahkan peristiwa kerusuhan Mei 1998. Penceritaan terfokus pada tindak kejahatan dan amoral yang dilakukan sekelompok orang kepada Clara, seorang gadis Indonesia keturunan Cina. Latar sejarah yang nyata menimbulkan pertanyaan tentang penggambaran ironi dengan logika realitas yang terkandung di dalam cerpen ini. Kajian terhadap cerpen ini bertujuan untuk menjelaskan hal itu. Analisis dilakukan dengan memanfaatkan teori struktur formal dan menerapkan pendekatan sosiologis dalam menginterpretasikan maksud tersirat pengarang. Hasil analisis menunjukkan bahwa dalam cerpen ini terdapat beberapa deskripsi ironi yang terjadi di Indonesia, yaitu: korupsi yang membuat negeri kaya raya ini tampak miskin dan tidak berdaya, rekayasa laporan, dan petugas penyedia informasi yang justru menyembunyikan informasi ketiga hal ini dilakukan oleh petugas berseragam. Ironi yang dilakukan oleh masyarakat ialah kebencian kepada etnis tertentu tanpa melihat orang tersebut baik atau tidak. Sementara itu, logika realitas dalam cerpen "Clara" berkesesuaian dengan realitas dalam berita yang terdapat di media massa. Penceritaan secara tersirat memberikan penyeimbang antara prasangka negatif yang berkembang dalam masyarakat pascakejadian dengan berita-berita media berdasarkan kesaksian beberapa narasumber.